Akselerasi Sistem Tol Laut Melalui Konsep Storage Island guna Pemberdayaan Wilayah Kecil Sebagai Pusat Logistik Berikat - Fazal Akmal Musyarri; Andriani Larasati; Paradisa Eksata Gheosa (Badan Perencanaan, Penelitian dan Pengembangan Pemerintah Provinsi Kepulauan Riau, 2024)
The national development orientation is starting to lean towards marine-based development, to reduce regional growth disparities, especially in the Eastern Region of Indonesia. The government has set the Maritime State Concept as a development priority, where one of the five pillars of the concept is the development of maritime infrastructure and connectivity. The main focus in this concept pillar includes the idea of sea highways and policies in the national logistics system. The solution being developed by the government is to build a Bonded Logistics Center (PLB) as a multifunctional logistics warehouse to stockpile imported or local goods. However, currently PLB development is still focused on sea ports, land ports and industrial areas in several regions in Indonesia. This limitative implementation reduces the efficiency of implementing PLB in Indonesia. So the author recommends the grand design of